Populism, Media Messaging, and Media Literacy - Tomšič Matevž (Politics in Central Europe, 2023)
The article deals with the rise of populism in connection with the functioning of the media and the role of media literacy in the receptivity of citizens to populist messages. The assumption is that the media play a dual role in this context: on the one hand, they make people susceptible to populist messages, and on the other hand, they can train them to become resistant to them. The quality of media communication affects the level of media literacy, i.e. the ability of people to understand and reflect on messages that are being disseminated by mass media, both traditional and online ones. The author claims that media literacy is the main protection against negative media phenomena such as disinformation and fake news. At the same time, it makes citizens resilient to those political messages that contain these elements on which populist politics is often based.